Industrialization under new WTO law - Amsden, Alice H. (UN New YorkUS, 1999)
Addresses the issue of whether late industrializing countries, including those with modest manufacturing experience as well as those which have success fuolly promoted manufacturing over the last 50 years, can continue to build their manufacturing ssectors under new WTO rules.